Joshua: an introduction and study guide : crossing divides - McConville, J. G. (T & T Clark study guides to the Old Testament, 2020)
Outline -- Joshua in literary criticism -- Joshua as literature -- Joshua and genre: history and myth -- Joshua and theology -- Joshua today.